Effective Safeguarding for Children and Young People What next after Munro? - Blyth, Maggie; Solomon, Enver (Bristol ; Chicago : Policy Press, 2012)
This timely book takes a critical look at the impact of the Munro Review (2011) on child protection and the Government's response.
Includes bibliographical references and index.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
Master record variable field(s) change: 072
Keywords: Munro, Eileen, -- 1950-; Munro, Eileen, -- 1950-; Child welfare -- Great Britain; Child welfare -- Government policy -- Great Britain; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE / Social Work; Electronic books